Effects of post-drying methods on pomelo fruit peels - Abd Rahman, Nur Farhana; Shamsudin, Rosnah; Ismail, Amin; Abdul Karim Shah, Nor Nadiah (Korean Society of Food Science and Technology, 2016)
Changes in physicochemical properties of moisture, ash, and fat contents, and color, due to freeze and oven post-drying treatments on flavedo, albedo, and lamella pomelo fruit peels were investigated. Physicochemical properties influence consumer acceptability and only a few studies are known. Pomelo peels were subjected to freeze drying and conventional drying at 60°C. Fresh pomelo peel was used as a control. Post-drying treatment changes in moisture, ash, and fat contents were observed, compared to controls. Minimal color changes were observed for freeze drying, compared with oven drying for flavedo, albedo, and lamella. Useful information for evaluation of drying treatments that can be used on pomelo peels is provided.